NILAI PERUSAHAAN : INTELLECTUAL CAPITAL DENGAN KINERJA KEUANGAN SEBAGAI PEMEDIASI - Jessica, Juliana; Rejeki, Dewi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
This study aims to examine the influence of VACA, VAHU and STVA on Company Value both directly and indirectly with Financial Performance as its moderator. The research was conducted on Banking Sector companies listed on the Indonesia Stock Exchange in 2020-2022 using a sample determination method using purposive sampling. The sample obtained was 34 companies with 102 observations. The technical analysis used in this study is descriptive statistics, classical assumption test, multiple regression test, hypothesis test and sobel test conducted using SPSS 26. The results of the study show that directly, only VACA has a positive and significant effect, while VAHU, STVA and Financial Performance have a negative effect on Company Value. Indirectly, VACA, VAHU and STVA have a positive and significant effect on the Company's Value through Financial Performance.